Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan DanSikap Pasien Tentang Pengelolaan Diet Diabetes MellitusDi Puskesmas Boyolali I - Pratama, Permadi Aziz, Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2016)
DM patients enrolled in the clinic boyolali still many who do not know the what the DM disease and what causes it and how to overcome them. It can be seen from the ignorance of the patient in answering questions when done frequently asked questions about DM, besides there are still many patients who do not control their diet, so it can improve blood sugar levels in the body that can worsen the patient's condition. Therefore health education is a good way to provide information, knowledge and attitudes of patients with diabetes mellitus for the better, so as not to 2 worsen the condition of patients with diabetes mellitus. The population in this study were 111 patients suffering from DM. The purpose of this study was to determine whether there is influence of health education on knowledge and attitude of the patients on how to manage diet DM in Puskesmas Boyolali I. This type of research is quantitative data in the form of numbers, using the method of pre experiment with pretest - posttest Design , The samples in this study using a random sampling totaling 53 people. The research instrument used questionnaire, health education leaflets media. Analysis of the data in this study using the Wilcoxon Rank Signeg. Wilcoxon Rank Signeg includes test nonparametric statistics with dependent variables of knowledge and attitude of the client while the variable independenya health education on the management of diet DM. The results showed a significant difference between knowledge and attitudes before and after health education with the Sig 0,000. The results of this study showed that health education leaflets method can effectively increase the knowledge and attitude of DM patients in Puskesmas Boyolali 1